Public Perception of Environmental and Sustainability Issues in North Sumatra: A Mass Media Perspective - Mhd Zikri Affandi Nasution; Hafidzsha Aqilla Mutiara Safirra; Ahmad Salman Farid (LPPM Universitas PGRI Sumatera Barat, 2023)
This research aims to understand public perceptions of environmental and sustainability issues in North Sumatra through a mass media perspective. The focus of this research is to analyze how the mass media depicts environmental and sustainability issues, as well as how public perceptions are formed through media exposure. A qualitative approach was used by interviewing respondents representing various levels of society in North Sumatra, while mass media content analysis was used to look at the representation of environmental and sustainability issues in the media. The research results show that mass media has a significant role in shaping public perceptions of environmental and sustainability issues in North Sumatra. Research finds that the mass media tends to provide limited coverage of environmental issues, focusing on controversial events or cases. This results in broader environmental problems, such as climate change, forest degradation and energy sustainability, not receiving enough attention in media coverage. The novelty obtained from this research is that sensationalism, consumer interests, limited resources, and the influence of personal interests are factors that can influence mass media reporting on environmental issues in North Sumatra.